2019
DOI: 10.2166/wst.2019.195
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive review on wastewater discharged from the coal-related industries – characteristics and treatment strategies

Abstract: Wastewaters discharged from various coal-related activities deteriorate fresh water quality and inflict possibilities of groundwater contamination. Their characteristics mostly depend on the parent coal properties, though some of the pollutants are cyanide, thiocyanate, ammonia, phenol, heavy metals and suspended solids. This paper has reviewed the treatment techniques along with the characteristics of all such kinds of wastewater and also identified the challenges and future perspectives. Primarily, demineral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 52 publications
0
31
0
Order By: Relevance
“…Nevertheless, other compounds such as acetate or butyrate, which could be used by microorganisms as carbon and energy sources (CES), are also present in coal gasification wastewater as common contaminants (Singer et al, 1978;Blum et al, 1986;Ji et al, 2016). Besides, it has been reported that coalrelated industries wastewaters have a high concentration of total dissolved solids, ranging from 174 to 2,000 mg•L −1 (Maiti et al, 2019). Furthermore, under closed-water-loops, increasing salinity in the wastewater is expected.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, other compounds such as acetate or butyrate, which could be used by microorganisms as carbon and energy sources (CES), are also present in coal gasification wastewater as common contaminants (Singer et al, 1978;Blum et al, 1986;Ji et al, 2016). Besides, it has been reported that coalrelated industries wastewaters have a high concentration of total dissolved solids, ranging from 174 to 2,000 mg•L −1 (Maiti et al, 2019). Furthermore, under closed-water-loops, increasing salinity in the wastewater is expected.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these compounds are volatile under the conditions present in raw wastewater (Kjeldsen 1999;Zhu et al 2018); therefore, a direct exposure to such liquids constitutes a serious risk to human health. The composition of coke plant effluents depends mainly on the quality of coals used and the operating and technological parameters of coke ovens (Maiti et al 2019;Zhu et al 2018) (Table 1).…”
Section: Composition Of Coke Plant Effluentsmentioning
confidence: 99%
“…Various techniques available combine different physical, chemical and biological processes, and the biological unit is an almost indispensable part of a successful and costeffective treatment process (Zhao and Liu 2016;Zhu et al 2018). In general, up to 90-99% reduction in contaminants can be achieved (Kim et al 2008a;Maiti et al 2019;Tong et al 2018;Zhu et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, raw COW is characterized by high contents of Chemical Oxygen Demand (COD), Biochemical Oxygen Demand (BOD), phenol, ammoniacal-N (NH 4 þ ), cyanide, sulfide, and thiocyanate (Kwiecinśka-Mydlak et al 2019). While the physico-chemical methods such as pH neutralization, flow equalization, coagulation, and chemical oxidation were used as primary treatment for reduction of COD to BOD ratio of coke-oven wastewater, membrane-based technique, ion exchange separation, electro-coagulation, photocatalysis, and adsorption in general, were used as a tertiary treatment method or as a polishing method in effluent treatment plant (Maiti et al 2019). Coagulation and precipitation methods and chemical oxidation methods are having disadvantages of high chemical cost, generation of sludge, and inefficiency to remove pollutants at ppm level (Waghmare & Arfin 2015).…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%